2018
DOI: 10.3389/fimmu.2018.02234
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Nucleoporin Nup210 Develop Peripheral T Cell Alterations

Abstract: The nucleopore is an essential structure of the eukaryotic cell, regulating passage between the nucleus and cytoplasm. While individual functions of core nucleopore proteins have been identified, the role of other components, such as Nup210, are poorly defined. Here, through the use of an unbiased ENU mutagenesis screen for mutations effecting the peripheral T cell compartment, we identified a Nup210 mutation in a mouse strain with altered CD4/CD8 T cell ratios. Through the generation of Nup210 knockout mice w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…In response to a foreign ECM environment, metastatic cells may exploit this mechanism through repositioning TADs to the nuclear pore for robust transcription of mechanosensitive genes, which then promote their migration into distant organs in an autocrine fashion. In fact, two recent studies have suggested that Nup210-deficient mice possesses defective T-cell receptor signaling 64,75 . It is highly likely that NUP210 might promote metastasis through rapid transcriptional activation of mechanosensitive, immune component genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to a foreign ECM environment, metastatic cells may exploit this mechanism through repositioning TADs to the nuclear pore for robust transcription of mechanosensitive genes, which then promote their migration into distant organs in an autocrine fashion. In fact, two recent studies have suggested that Nup210-deficient mice possesses defective T-cell receptor signaling 64,75 . It is highly likely that NUP210 might promote metastasis through rapid transcriptional activation of mechanosensitive, immune component genes.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from providing structural support and nucleocytoplasmic transport 57 , the role of the nuclear pore complex in developmental gene regulation has drawn much attention recently [58][59][60][61] . Although NUP210 has been implicated in muscle differentiation 28,62 , cellular reprogramming 63 , and T cell signaling 64,65 , its function in human cancer was unknwon. Here, we have identified Nup210 as a potential metastasis susceptibility gene for human ER+ breast cancer patients and demonstrated a previously unrecognized role of nuclear pore proteins in sensing the mechanical stress of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two independent studies have revealed a role for the transmembrane Nup Nup210 in T-cell homeostasis (Borlido et al, 2018;van Nieuwenhuijze et al, 2018). Loss of Nup210 has been found to cause a severe decrease in the naïve CD4 + T-cell population.…”
Section: Box 2 Npcs Aging and Neurodegenerationmentioning
confidence: 99%
“…In Drosophila, another cytoplasmic filament protein Mbo (the homolog of human Nup88) is required for the immune response against bacterial infection. Besides leading to alterations in the CNS, oogenesis and tracheal development, ablation of mbo results in a severe immune deficiency, owing to alterations in the nuclear import of factors key for the activation of the immune response (Uv et al, 2000).…”
Section: Box 2 Npcs Aging and Neurodegenerationmentioning
confidence: 99%